Strategies for Strengthening the Competitiveness of MSMEs in Driving Economic Growth in Border Areas in the Digital Era and Regional Market Integration - Evin Juliasti (CV Edujavare Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in promoting economic growth, employment generation, and regional development, particularly in border areas that serve as strategic gateways for cross-border economic activities. However, MSMEs in border regions often face challenges related to limited infrastructure, restricted market access, low technological adoption, and increasing competition within integrated regional markets. This study aims to analyze strategies for strengthening the competitiveness of MSMEs in driving economic growth in border areas within the context of the digital era and regional market integration. The research employs a literature review approach by examining relevant scholarly articles, books, institutional reports, and conference proceedings published between 2015 and 2025. The findings indicate that digital transformation is a critical factor in enhancing MSME competitiveness through improved market access, operational efficiency, innovation, and customer engagement. Furthermore, regional market integration provides opportunities for MSMEs to participate in broader markets and regional value chains, thereby increasing their growth potential. However, realizing these benefits requires supportive policies, digital infrastructure development, financial inclusion, entrepreneurial capacity building, and collaborative governance involving multiple stakeholders. The study concludes that strengthening MSME competitiveness through digitalization and regional integration is essential for fostering sustainable economic growth, improving regional connectivity, and enhancing the economic resilience of border communities